2018
DOI: 10.15809/irriga.2018v23n1p34
|View full text |Cite
|
Sign up to set email alerts
|

Produção E Respostas Fisiológicas Da Mangueira Cv. Keitt Sob Diferentes Sistemas De Irrigação No Submédio Do São Francisco

Abstract: PRODUÇÃO E RESPOSTAS FISIOLÓGICAS DA MANGUEIRA CV. KEITT SOB DIFERENTES SISTEMAS DE IRRIGAÇÃO NO SUBMÉDIO DO SÃO FRANCISCO  WELSON LIMA SIMÕES1; PEDRO PAULO BEZERRA FERREIRA2; MARIA APARECIDA DO CARMO MOUCO3; MARIA AUXILIADORA COELHO DE LIMA4; MIGUEL JULIO MACHADO GUIMARÃES5 E JOSÉ ALIÇANDRO BEZERRA DA SILVA6  1 Embrapa Semiárido, rodovia BR-428, Km 152, s/n, Zona Rural, EMBRAPA, Petrolina, PE, CEP 56302-970. E-mail: welson.simoes@embrapa.br2 Universidade Federal do Vale do São Francisco, UNIVASF, Juazeiro, BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Thus, the bulbshaped wetted area of the treatment MSBP was formed under a little shaded area subjected to high evaporation rates, thus decreasing the soil water potential and water availability to plants. Similar results were found bySimões et al (2018) for Keitt mango trees, and bySimões et al…”
supporting
confidence: 90%
“…Thus, the bulbshaped wetted area of the treatment MSBP was formed under a little shaded area subjected to high evaporation rates, thus decreasing the soil water potential and water availability to plants. Similar results were found bySimões et al (2018) for Keitt mango trees, and bySimões et al…”
supporting
confidence: 90%
“…The results in Figure 2 show that both excess and scarcity of water caused partial closure of the stomata, which is an essential mechanism for plant survival under different soil moisture conditions (Simões et al, 2018;Ghafari et al, 2020;Gupta et al, 2020;Li et al, 2020). The highest levels of photosynthesis (Figures 2A and D), stomatal conductance (Figures 2B and E) and transpiration (Figures 2 C and F) in the cultivation with the rootstock were estimated for irrigation of 107.4, 108.3, and 117.3% ETc in the first half of the year and 114.4, 117.5, and 112.0% in the second half of the year, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient as well as excessive water supply induces stomatal closure, thus avoiding the reduction in the water potential. However, this response negatively affects various physiological processes such as transpiration and photosynthesis, causing a reduction in fruit weight (Simões et al, 2018). Regarding production, there was interaction between the forms of cultivation and the production cycles (Figure 5).…”
Section: Table 1 Summary Of Analysis Of Variance Of the Variables Ana...mentioning
confidence: 99%
“…Thus, the irrigation cycle with micro-sprinklers was not sufficient for the roots to develop throughout the wetted profile, since the irrigation amounts were the same and with a deficit. Simões et al (2018) evaluated the effect of the micro-sprinkler and drip-irrigation systems on the physiological, productive and qualitative traits of fruits of 'Keitt' mango tree at nine years old and found that drip irrigation is the most suitable system for its cultivation, in Vale do Submédio São Francisco, because it interferes positively with photosynthetic activity, stomatal conductance and yield.…”
Section: Yield and Water Use Efficiency Of 'Palmer' Mangomentioning
confidence: 99%
“…The lower WUE in the micro-sprinkler system may be related to the form of water distribution in the soil, since the micro-sprinkler is located far from the plant trunk and part of the soil moistened by the irrigation system is exposed to solar radiation, which can increase evaporation losses and reduce water availability for the plant, as compared with drip irrigation (Simões et al, 2018). In addition, the drip irrigation system allows less evaporation of water from the soil when compared with the micro-sprinkler, especially in regions with strong winds that coincide with the period when irrigation is necessary, as is the case in the evaluated region (Figure 1).…”
Section: Yield and Water Use Efficiency Of 'Palmer' Mangomentioning
confidence: 99%